Triterpenes and lignans from the leaves of Styrax tonkinensis. (October 2019) - Hu, Wan-Li; Li, Zhen-Lin; Chen, Qiu-Jing; Sun, Yue-Wen; Zhai, Shuo; Lu, Fang; Li, Fei; Zhang, Chun-Feng
Abstract: Two triterpenes (1 and 2) and eight lignans (3–10) were isolated from the ethyl acetate-soluble fraction of the leaves of Styrax tonkinensis (Pierre) Craib ex Hartw (Styracaceae). Their structures were established as ursolic acid (1), pomolic acid (2), 3, 3′-bis(3, 4-dihydro-6-methoxy-2H-1-benzopyran) (3), rac-(8α, 8′β)-4, 4′-dihydroxy-3, 3′-dimethoxylignan-9, 9′-diyldiacetate (4), (-)-secoisolariciresinol (5), (+)-pinoresinol (6), 4, 4′-dihydroxy-3, 3′-dimethoxy-9-ethoxy-9, 9′-epoxylignan (7), (2S, 3R, 4R)-4-[1-ethoxy-1-(4-hydroxy-3-methoxy)phenyl]methyl-2-(4-hydroxy-3-methoxy)phenyl-3-hydroxymethyl-tetrahydrofuran (8), (-)-neo-olivil-(9-O-9″)-seco-isolariciresinol (9) and isolariciresinol (10) based on MS, 1 H-and 13 C-NMR spectral data. All these compounds (1–10) were firstly isolated from this plant, and compounds 2–5 and 7–9 were reported from the Styrax genus for the first time. Furthermore, the chemotaxonomic significance of the isolated compounds was discussed. Graphical abstract: Image 1 Highlights: Ten compounds (1–10) were isolated from the leaves of Styrax tonkinensis. These included two triterpenes and eight lignans. The chemotaxonomic significance of the isolated compounds was discussed.